Abiotic Indicators of Climate Change in Indian Sundarbans - Mitra, Abhijit; Zaman, Sufia; Chakraborty, Rajiv; Haider, Piu; Banerjee, Kakoli (Indian Science Cruiser, 2009)
Coastal zones are particularly vulnerable to climate variability and change. Key concerns include sea level rise, land loss, changes in maritime storms and flooding, responses to sea level rise and implications for water resources. The IPCC estimates that the global average sea level will rise between 0.6 and 2 feet (18 to 59 cm) in the next century. India has been identified as one amongst 27 countries, which are most vulnerable to the impacts of global warming - induced sea level rise. Any global warming-induced climatic change such as increase in sea surface temperature, change in frequency, intensity or tracks of cyclones, sea level rise may aggravate the potential risks to coastal zones and estuarine systems of the Indian sub-continent. The adverse impact of climate change on estuarine system stems from the fact that global warming may cause changes in the salinity level of the coastal and estuarine waters, the amount of , oxygen in the water, pollution level and turbidity levels due to increased frequency of erosion caused by amplified tidal amplitude. On this background, an investigation was undertaken in the aquatic system of mangrove dominated Indian Sundarbans considering surface water temperature, salinity and dissolved oxygen as indicators. Possible adverse impacts on the human society due to such change have also been highlighted.